Peningkatan kemampuan berfikir kritis melalui model pembelajaran Probing Promting Berbantu Board Game pada kelas VII-10 SMP Negeri 10 Palembang - Saputra, Ardiansyah (Journal of Innovation in Teaching and Instructional Media, 2024)
The low critical thinking skills of students found by us when conducting observations at SMP Negeri 10 Palembang have an impact on the learning process of students becoming passive and have an impact on the grades produced by students as seen from the lack of answering when given questions and then learning outcomes that still do not meet the criteria for teaching completion. This study used the Classroom Action Research method which was applied to class VII-10 of SMP Negeri 10 Palembang with a total of 36 students. The implementation of this study includes 3 cycles in it which include planning, acting, and observing. The instruments used in this study were observation sheets and pretest posttests which were carried out in each cycle. Based on the results obtained in this study, it was found that there was an increase in students' critical thinking skills using the probing prompting learning model which was proven by an increase in each learning cycle carried out.